(untitled) (Світ фінансів, 2017)
Лютий І. О., Курищук К. К. Механізм внутрішніх державних запозичень України. Запропоновано механізм внутрішніх державних запозичень, охарактеризовано суб’єкти й об’єкти внутрішніх державних запозичень, систему, методи та інструменти управління внутрішнім державним боргом, джерелами погашення внутрішнього державного боргу. Визначено імперативи управління внутрішнім державним боргом у розрізі ефективного макроекономічного регулювання, а саме: вплив на обсяг сукупних витрат через запровадження ефективних інструментів бюджетної та податкової політики держави; адекватність режиму валютного курсоутворення; дієвість інструментів грошово-кредитної політики щодо забезпечення цінової стабільності. Лютый И. А., Курищук К. К. Механизм внутренних государственных заимствований Украины. Предложен механизм внутренних государственных заимствований, охарактеризованы субъекты и объекты внутреннего государственного долга, система, методы и инструменты управления внутренним государственным долгом, источники погашения внутреннего государственного долга. Определены императивы управления внутренним государственным долгом в разрезе эффективного макроэкономического регулирования, а именно: влияние на объем совокупных расходов через внедрение эффективных инструментов бюджетной и налоговой политики государства; адекватность режима валютного курсообразования; действенность инструментов денежно-кредитной политики относительно обеспечения ценовой стабильности. Ljutyi I., Kuryschuk K. The mechanism of internal government borrowings of Ukraine. Introduction. The authors propose a mechanism of internal government borrowings of Ukraine. Described subjects and objects of domestic public debt, the system, methods and management tools domestic public debt, sources of repayment of the domestic public debt. Purpose. According with the priorities of the internal debt policy of Ukraine, define the objectives and tasks of the internal management of the public debt. Management determined the imperatives of domestic public debt in the context of effective macroeconomic management, namely the impact on the volume of total expenditure through the introduction of effective tools for budgetary and fiscal policies of the state; the adequacy of the currency exchange rate regime; the effectiveness of the tools of monetary policy on ensuring price stability. Mechanisms of internal of public borrowing Ukraine is proposed to consider a set of forms, methods, techniques and procedures of targeting of domestic government borrowing on domestic of public borrowing objects through government domestic debt management to ensure the stability of the financial system of the state. In the system of government domestic debt proposed to separate the institutional subsystem, legal subsystem and technological subsystem. Results. It is proved that the methods of government domestic debt management should be integrated into the budget mechanism through the operation of the state budget related to the change of the domestic public debt, its maintenance, management and use of borrowed funds; based on historical and economic conditions and market mechanisms of the financial system; cover accounting system domestic public debt; tailored to suit market pricing of domestic government borrowing; have a purpose build forecasts objective changes in the value of domestic government borrowing. Conclusion. Proved that the level of macroeconomic management, the internal public debt management tool is the formation and distribution of national income for the purpose of leveling contradictions between economic and social needs of society.